Reviews of new publications - Holmes, Derek A (KUKILA, 1990)
Mason, V. and F. Jarvis. 1989. Birds of Bali. Berkeley and Singapore: Periplus Editions. 80pp   Howes, J. & D. Bakewell. 1989. Shorebird Studies Manual. AWB Publication No.55, Kuala Lumpur   Eve, R. & Guigue, A.M. 1989. Survey of the Mahakam River Delta, East Kalimantan -with special reference to its waterbirds. Asian Wetland Bureau publication no. 45, Kuala Lumpur. 34 pp